Umroh Backpacker: Prospek, Kendala Dan Strategi Pengembangannya - Kusumaningtyas, Menur (STIE Mahardhika, 2018)
Umroh as one of the instruments of Islamic worship in Indonesia seems to be prospective compared to the others. The indication of its development is started in the practice of the law related to its such as Undang-Undang No. 13 of 2008 on the Implementation of Hajj (